STRATEGIC MILITARY COLONISATION: THE CAPE EASTERN FRONTIER 1806–1872 - Robson, Linda; Oranje, Mark (Scientia Militaria - South African Journal of Military Studies, 2012)
The Cape Eastern Frontier of South Africa offers a fascinating insight into British military strategy as well as colonial development. The Eastern Frontier was for over 100 years a very turbulent frontier. It was the area where the four main population groups (the Dutch, the British, the Xhosa and the Khoikhoi) met, and in many respects, key decisions taken on this frontier were seminal in the shaping of South Africa. This article seeks to analyse this frontier in a spatial manner, to analyse how British settlement patterns on the ground were influenced by strategy and policy. The time frame of the study reflects the truly imperial colonial era, from the second British occupation of the Cape colony in 1806 until representative self-governance of the Cape colony in 1872.